2013
DOI: 10.1007/s00382-013-1976-5
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling over Vietnam using the stretched-grid CCAM: verification of the mean and interannual variability of rainfall

Abstract: Rainfall over Vietnam is highly variable from north to south, due to the interaction of the monsoonal winds with the terrain. There is high rainfall from April to September, and little rainfall from October to March (except along the central Vietnam coast). In order to study the ability of the Commonwealth Scientific and Industrial Research Organisation stretched-grid Conformal Cubic Atmospheric Model (CCAM) to capture the climatic and interannual variability of rainfall, downscaled simulations at approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
(35 reference statements)
2
12
0
Order By: Relevance
“…Compared with previous studies, we found similar results to Nguyen et al (2014b) and Katzfey et al (2016), which used two RCMs as a downscaling tool for precipitation for this area. In their studies, simulations show generally lower rainfall amounts at the north central coast of Vietnam compared with observational datasets and an overestimation of rainfall in south Vietnam, which corresponds to the findings of our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Compared with previous studies, we found similar results to Nguyen et al (2014b) and Katzfey et al (2016), which used two RCMs as a downscaling tool for precipitation for this area. In their studies, simulations show generally lower rainfall amounts at the north central coast of Vietnam compared with observational datasets and an overestimation of rainfall in south Vietnam, which corresponds to the findings of our study.…”
Section: Discussionsupporting
confidence: 87%
“…Compared with previous studies, we found similar results to Nguyen et al . () and Katzfey et al . (), which used two RCMs as a downscaling tool for precipitation for this area.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the continental freshwater discharge of the Red River is strongly influenced by the South Asia Summer Monsoon (SASM) (Isupova and Mikhailov, 2011) with seasonal characteristics (Simonovic and Carson, 2003). EI Niño Southern Oscillation (ENSO) can also trigger occurrence of some extreme hydroclimatological events in rivers, such as floods, droughts and precipitation anomalies (Zhang et al, 2013a;Nguyen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies (Kim et al 2014;Dosio et al 2015;Kotlarski et al 2014;Nguyen et al 2014) focused on the assessment of model simulations over different spatial and temporal scales are already available in the literature. Simulations performed for the Coordinated Regional Climate Downscaling Experiment (CORDEX) were evaluated by Kim et al (2014) over the African region using gridded station data from the Climate Research Unit (CRU).…”
Section: Introductionmentioning
confidence: 99%
“…They noted that seasonally and regionally averaged temperature biases are small while precipitation biases are large. Nguyen et al 2014 evaluated interannual variability of rainfall produce by CCAM simulations over the Vietnam region by comparing with APHRODITE data. They found that the CCAM simulations performed better for North and Central Vietnam than for South Vietnam.…”
Section: Introductionmentioning
confidence: 99%